The Competence of Islamic Religious Education Teachers Perspective K.H. Hasyim Asy'ari - Tasurun Amma; M. Saiful Bahri; Ahmad Munawir (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
A professional teacher is meets several classifications, including the individual is a teacher with recognized, has teacher expertise or what is often called expertise in certain scientific fields related to his profession as a teacher, fulfills the aspects of coaching and development. who go through formal education or non-formal coaching. This research focuses on the competence of Islamic Religious Education teachers in the perspective of Kiai H. Hasyim Asy'ari, especially referring to his book Adabu Al-Alimi Wal Muta'alim. This type of research uses a type of library research. The primary data is from Adabu Al-Alimi Wal Muta'alim The results of this study are three teacher positions according to KH. Hasyim Asy'ari, namely teachers as individual teachers regarding personal religious, teachers when teaching, and teachers to students. The pedagogic competence indicator according to KH. Hasyim Asy'ari includes the attitude of purifying himself from all things that are not blessed by Allah Almighty, visionary, and having knowledge. Personality competence covers a calm person, tawakal, tawadhu ', and an independent person ,. Professional competence according to KH. Hasyim Asy'ari is a teacher's ability in knowledge and good at managing class. Social competence, according to KH. Hasyim Asy'ari is good at choosing jobs, good at choosing communities where to gather, avoiding places that socially can reduce the degree of teachers, and able to interact well.